Kebijakan Pembangunan Ibu Kota Negara sebagai Strategi Pencapaian Tujuan Pembangunan Berkelanjutan di Indonesia - Azizah, Nur; Burhan, M. Ghiffari Ramadhan; Irwansyah, Irwansyah; Sagena, Uni W.; Masjaya, Masjaya (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This study aims to evaluate the implementation of the Nusantara Capital development planning policy as a strategy to accelerate the achievement of the development of sustainable cities and communities. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that the development of the Nusantara Capital has been strategically integrated with the SDGs. A solid legal and policy foundation has facilitated a holistic approach in planning and implementing this project, covering everything from efficient spatial organization to sustainable resource management. This policy implementation demonstrates a solid commitment to sustainable development principles, including environmentally friendly infrastructure development, social integration, and community participation. Moreover, the development of the Nusantara Capital explicitly supports the achievement of the development of cities and communities, which aims to create inclusive, safe, resilient, and sustainable urban environments. This approach ensures that development targets such as adequate housing, sustainable transportation, cultural heritage preservation, and environmental management are holistically integrated, meeting long-term objectives while addressing urbanization challenges. Therefore, it is recommended that the government should continue to strengthen policies and regulations that support sustainable development practices, ensuring transparency and accountability in every phase of development. For the private sector and industry, it is highly advisable to invest in environmentally friendly technologies and sustainable practices that support the vision of the Nusantara Capital as a model for future cities. Meanwhile, the community should be actively involved in the planning and decision-making processes to ensure that development is inclusive and meets local needs. Cooperation among all parties is essential to achieve inclusive, safe, resilient, and sustainable development goals, in line with SDG 11.